2017
DOI: 10.1016/j.fbr.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Climate change, food security and mycotoxins: Do we know enough?

Abstract: Climate change (CC) scenarios are predicted to have significant effects on the security of staple commodities. A key component of this impact is the infection of such crops by mycotoxigenic moulds and contamination with mycotoxins. The impacts of CC on mycotoxigenic fungi requires examination of the impacts of the threeway interactions between elevated CO2 (350-400 vs 650-1200 ppm), temperature increases (+2-5 o C) and drought stress on growth/mycotoxin production by key spoilage fungi in cereals and nuts. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
178
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 217 publications
(188 citation statements)
references
References 53 publications
(66 reference statements)
4
178
0
6
Order By: Relevance
“…Furthermore, there has also been an increasing concern that climate change permits for the increased propagation of crop pests and pathogens and their movement to other previously unsuitable regions (Bebber, Ramotowski, & Gurr, ) due to the alteration in the natural environments, which creates new opportunities for evolution (Fisher et al., ). The impacts of climate change on the propagation of microfungi, especially that of the mycotoxigenic fungi and the subsequent mycotoxin production, have been previously discussed in depth (Botana & Sainz, ; Ksenija, ; Medina, Akbar, Baazeem, Rodriguez, & Magan, , ; Paterson & Lima, , ).…”
Section: Emerging Challenges In Mycotoxin Managementmentioning
confidence: 99%
“…Furthermore, there has also been an increasing concern that climate change permits for the increased propagation of crop pests and pathogens and their movement to other previously unsuitable regions (Bebber, Ramotowski, & Gurr, ) due to the alteration in the natural environments, which creates new opportunities for evolution (Fisher et al., ). The impacts of climate change on the propagation of microfungi, especially that of the mycotoxigenic fungi and the subsequent mycotoxin production, have been previously discussed in depth (Botana & Sainz, ; Ksenija, ; Medina, Akbar, Baazeem, Rodriguez, & Magan, , ; Paterson & Lima, , ).…”
Section: Emerging Challenges In Mycotoxin Managementmentioning
confidence: 99%
“…In the future the effect of climate change may affect growth of these toxigenic fungi and hence mycotoxin production, as environmental conditions including temperature, relative humidity, increased CO2 and sunlight affect their survival. The climate change effects on fungal survival and mycotoxin production have been discussed elsewhere [38]. Certainly, interactions between these three factors have been shown to stimulate aflatoxin B production by A. flavus, and RNAseq has shown that gene clusters related to secondary metabolite production, stress related functional genes and sugar tranporters amongst others were important [39].…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…The globalization of world economics, with huge traffic flows, creates favorable conditions for dissemination of contaminated foodstuffs around the world [5]. Global warming stimulates the formation and dissemination of mycotoxins [6]. Besides, they are not easily eliminated in food processing because of their stability against heat, physical, and chemical treatments [7].…”
Section: Introductionmentioning
confidence: 99%